1988
DOI: 10.1111/j.1600-0676.1988.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver cirrhosis in histiocytosis X

Abstract: ABSTRACT— Cirrhosis of the liver was diagnosed in an 18‐year‐old man with histiocytosis X. Electron microscopy and immunohistochemistry revealed infiltration of the liver by the typical cellular elements of histiocytosis X. Endoscopic retrograde cholangiography showed alterations resembling those of sclerosing cholangitis. Sixteen months later, the patient died of recurrent variceal bleeding and cholangiosepsis. Autopsy confirmed that cirrhosis was the main manifestation of the underlying disease. Thus, cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Conversely , the presence of 8-100-staining cells within portal tracts is not unique to LCH (12). Mural infiltration of large bile ducts by Langerhans ' cells with progressive ductal scarring produces the cholangiographic pattern of sclerosing cholangitis (4,5,10). Xanthomatous inflammation of the large intrahepatic bile ducts would not be detected by liver biopsy alone and could produce the portal fibrosis and ductal proliferation often observed in the liver of LCH patient s with hepatic dysfunction, as seen in this patient.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Conversely , the presence of 8-100-staining cells within portal tracts is not unique to LCH (12). Mural infiltration of large bile ducts by Langerhans ' cells with progressive ductal scarring produces the cholangiographic pattern of sclerosing cholangitis (4,5,10). Xanthomatous inflammation of the large intrahepatic bile ducts would not be detected by liver biopsy alone and could produce the portal fibrosis and ductal proliferation often observed in the liver of LCH patient s with hepatic dysfunction, as seen in this patient.…”
mentioning
confidence: 67%
“…Primary sclerosing cholangitis and LCH may have similar radiographic findings. Although ectasia and stenosis limited to the intrahepatic bile ducts are more typical of LCHassociated sclerosing cholangitis, sufficient overlap with primary sclerosing cholangitis exists to preclude a definitive diagnosis based solely upon the cholangiogram (5,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver involvement in adult LCH is relatively rare (6)(7)(8). Nagai et al reported 1 case of adult LCH with liver involvement (8) and reviewed 5 previously reported adult cases (9)(10)(11)(12)(13). Interestingly, in their case, radiographic findings of both the lungs and the liver displayed marked improvements after smoking cessation; the case was described as "PLCH with liver involvement".…”
Section: Discussionmentioning
confidence: 99%
“…In late stages, patients may present with severe sclerosing cholangitis and liver failure. A subset of patients progresses to develop cirrhosis, which may lead to portal hypertension and secondary hypersplenism[ 22 , 23 ].…”
Section: Clinical Manifestationmentioning
confidence: 99%